Hand hygiene practices among school children of a periurban area Firozabad district - Srivastava, Rajiv; Singh Mehta, Amarveer (International Journal Of Community Medicine And Public Health, 2018)
Background: Hand hygiene is a milestone of infectious disease control, and promotion of improved hand hygiene has been recognized as an important public health measure. The present study was undertaken to assess the hand hygiene practices among the school students of a peri urban area in district Firozabad. Methods: This six months cross sectional study was carried out among the students of an Intermediate college situated in a peri urban area of Firozabad district, U. P. All the students who were present in the respective classes (Vth–VIIth standard) were surveyed. A structured, self-administered pretested questionnaire was used to collect detailed information about the subjects‟ self-reported hand washing practices. Data entry and statistical analysis were performed using the Microsoft Excel and SPSS windows version 14.0 software. Results: Out of total 76 students, 97.4% practiced hand washing after defecation with Soap and water, while 63.2% did hand washing after cleaning with soap and water and 31.6% washed hands before eating food with Soap and water. A higher proportion of males showed proper hand hygiene practices than females. Proper Hand hygiene practices increased with the increase in education. Conclusions: Teaching the correct hand hygiene practice at an early age with help students to be healthy in later life. Thus primordial prevention is the key to reduce infection in school children.